2022
DOI: 10.1101/2022.03.01.22271254
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-SAFER: Deprescribing Guidance for Nirmatrelvir-ritonavir Drug Interactions in Older Adults

Abstract: ImportanceOlder adults, at high-risk of developing complications from COVID-19, could benefit from nirmatrelvir-ritonavir, an oral antiviral treatment for outpatients at high risk of complications from COVID-19; however, due to its potent CYP3A4 inhibition, nirmatrelvir-ritonavir is associated with many drug-drug interactions (DDI).ObjectivesIdentify how common DDIs are between nirmatrelvir-ritonavir, common medications, and PIMs in older adults with polypharmacy. Craft anticipatory deprescribing guidance for … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
3
1
Order By: Relevance
“…Within this study's cohort of patients receiving prescriptions, a substantial proportion of 75.3% (n=143) exhibited drug-drug interactions with Paxlovid ® that necessitated intervention. This percentage is higher than the results of another study, which indicated that 68.0% (n=3,869) of patients were prescribed medications with potential interactions with Paxlovid ® [29]. In this study, within the medications falling under the high-risk interaction category, simvastatin, a lipid lowering agent, was the most prevalent.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Within this study's cohort of patients receiving prescriptions, a substantial proportion of 75.3% (n=143) exhibited drug-drug interactions with Paxlovid ® that necessitated intervention. This percentage is higher than the results of another study, which indicated that 68.0% (n=3,869) of patients were prescribed medications with potential interactions with Paxlovid ® [29]. In this study, within the medications falling under the high-risk interaction category, simvastatin, a lipid lowering agent, was the most prevalent.…”
Section: Discussioncontrasting
confidence: 75%
“…In this study, a notable 75.3% (n=143) of the patient cohort faced drug-drug interactions with Paxlovid® that required proactive management. This incidence surpasses that reported in another research, where 68.0% (n=3,869) of patients were identi ed as taking medications potentially interacting with Paxlovid® [29]. Notably, within the category of high-risk interactions, simvastatin was most frequently implicated.…”
Section: Discussionmentioning
confidence: 51%
“…Older people are at higher risk for severe complications from COVID-19. Explanation of PIMs before COVID-19 infection can increase the relation of older people that can safely be given nirmatrelvir-ritonavir, in addition to the ordinary advantages seen with drug administration [50][51][52].…”
Section: Safety Of Nirmatrelvir In Patientsmentioning
confidence: 99%
“…Guidelines for deprescribing contain long lists of rules that preclude memorization; some may contain conflicting recommendations for patients taking 10 to 15 medications; and not all guidelines explain how to deprescribe (eg, when and how to taper and what rebound symptoms to watch out for). 2,[21][22][23] We therefore integrated the dialysis-specific deprescribing recommendations into the MedSafer ruleset, coupled them with links to patient deprescribing empowerment brochures, and added instructions for tapering where required.…”
Section: Background and Rationalementioning
confidence: 99%